Anatomical basis of distally based anterolateral thigh flap. Issue 3 (June 2014) - Yamada, Satoshi; Okamoto, Hideki; Sekiya, Isato; Wada, Ikuo; Kobayashi, Masaaki; Goto, Hideyuki; Mizutani, Jun; Nozaki, Masahiro; Hayashi, Katsuhiro; Murakami, Satona; Murase, Atsunori; Kawaguchi, Yohei; et al.
Abstract: Soft tissue coverage around the knee has persisted as a challenge for plastic and reconstructive surgeons. The distally-based anterolateral thigh flap is often used for coverage. Nevertheless, few anatomical studies have investigated the retrograde vascular pedicle. This report clarifies the anatomy of the connection between the descending branch of the lateral circumflex femoral artery and the lateral superior genicular artery. This study examined 38 lower limbs from cadavers and recorded the numbers and locations of perforating vessels. Proximal and distal pivot points were also recorded. The proximal pivot point was 1.0–12.1 cm (average = 6.0 cm) from the inguinal ligament. The distal pivot point, found under the vastus lateralis muscle in all 38 specimens, was 4.0–13.6 cm (average = 9.8 cm) from the lateral superior edge of the patella. The most distal perforator was 8.2–28.0 cm (average = 18.9 cm) from the proximal pivot point. The most proximal perforator was 3.0–19.5 cm (average = 8.7 cm) from the distal pivot point. Details of the anastomosis of the descending branch and the superior lateral genicular artery were clarified. The distally-based anterolateral thigh flap presents one option for reconstruction around the knee.